Pengaruh Penggunaan Media Video pada Konsep Sistem Kerangka Manusia Terhadap Motivasi dan Hasil Pembelajaran Kognitif Siswa SMAN I Peukan Baro Kabupaten Pidie - Fauzan Fauzan; Khairil Khairil; Safrida Safrida (Universitas Islam Negeri Ar-Raniry, 2018)
A study has been conducted to determine the differences in motivation and student learning outcomes by using video media and by conventional learning on Human Skeletal System subject at SMAN 1 Peukan Baro in Pidie Regency in 2016/2017 school year. The population of this study was 46 students. The entire population was selected as a research sample that is 23 students for the experimental class and 23 students for the control class. Motivation data and learning outcomes were collected through a pretest and posttest questionnaire. The learning outcomes were analyzed using the F test and Mann Whitney. The results showed that motivation and learning outcomes differed significantly between students who used video media learning and students who were teached conventionally with a P value of 0,000 < 0.05. In conclusion there are significant differences in motivation and learning outcomes between students who use video media learning and students who use conventional learning methods especially on the topic of the Human Skeletal System.